The Relationship of the Use of Powder in the Genetalia Area of Babies Aged 0-9 Months to the Event of Diaper Rash at PMB Fadilah, Bulukagung Madura Village - Miftahul Khairoh; Arkha Roosyaria B; Kholifatul Ummah (Formosa Journal of Science and Technology, 2022)
Diaper rash or often called diaper rash is a bright red rash caused by irritation of the skin exposed to urine or feces that lasts a long time under a child's diaper. This study analyzed the relationship between the use of loose powder in the genital area of ​​infants aged 0-9 months to the incidence of diaper rash in PMB Fadilah, Bulukagung Village, Madura. Correlation research, cross sectional, population of 23 infants aged 0-9 months with diaper rash, 23 infants sampled, purposive sampling, observation data collection, checklist measuring instrument, chi square analysis, (0.05). The results of statistical analysis with the chi square test, the results obtained = 0.000 with a level of 0.05 which means = 0.000 <0.05, so there is a relationship between the use of loose powder in the genital area of ​​infants aged 0-9 months to the incidence of diaper rash.